Social Integration as Catalyst for People's Prosperity - Ismail, Fadillah; Ismail, Zuhaimy; Azhar Abd Hamid, Mohd.; Mohamad, Ismail; Thukiman, Kassim (International Journal of Engineering and Technology, 2018)
In a nation-state, the aspect of unity among the people is important. Unity can define the political, economic and social stability. As a multi-racial country, Malaysia is a unique and special nation. Malaysia is regarded as an ideal country, a peaceful and happy country inhabited by various races and religions by other countries in the world. Due to its multi-racial status, it canâ€™t be denied that Malaysia faces some problems in sustaining the harmonious people. Various policies were formulated by the Federal Government and the State Government to address racial issues in Malaysia. In this regard, the article seeks to identify the level of social integration of the community in Johor. The findings show that the state of Johorian integrity is at a good level that is projected to an excellent level. In addition, the findings show that some elements need to be emphasized in empowering social integration in the state of Johor to avoid inter-racial tensions, especially in relation to the Rukun Negara that is not understood and practiced in a day-to-day life. The implication of this study is that social integration between the peoples is actually a catalyst for the welfare and at the same time improve the quality of life of the people of Johor. Hence, it is proposed that the Federal Government in collaboration with the State Government of Johor formulate various inclusive policies and have a close relationship with the people.Â Â